The problem of organizing defence actions in volleyball: analysing the results of questioneering high-quality players and trainers - Y V Shikhovtsov; A A Lobanov; I A Demidkina (RUDN Journal of Psychology and Pedagogics, 2009)
The article examines the factors influencing the defence strategy of the players, defence formations used by master-players are analyzed. The usage rational defence formations during volleyball competitions allows to increase effectiveness of defence actions.